1991
DOI: 10.1002/ana.410300505
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary branching enzyme dysfunction in adult polyglucosan body disease: A possible metabolic cause in two patients

Abstract: We describe 2 unrelated patients with adult polyglucosan body disease (APBD) diagnosed by sural nerve biopsy. Both patients were offspring of consanguineous marriages. They presented clinically with late onset pyramidal tetraparesis, micturition difficulties, peripheral neuropathy, and mild cognitive impairment. Magnetic resonance imaging of the brain revealed extensive white matter abnormalities in both. In search of a possible metabolic defect, we evaluated glycogen metabolism in these patients and their cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 32 publications
2
62
0
3
Order By: Relevance
“…Enzymatically, except for adult polyglucosan body disease (15,16), most GSD-IV patients have what appears to be a generalized enzyme defect. The deficiency of GBE activity and the accumulation of amylopectin can be demonstrated in almost all tissues studied, including liver, heart, skeletal muscle, brain, leukocytes, and fibroblasts (5, 9, 12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymatically, except for adult polyglucosan body disease (15,16), most GSD-IV patients have what appears to be a generalized enzyme defect. The deficiency of GBE activity and the accumulation of amylopectin can be demonstrated in almost all tissues studied, including liver, heart, skeletal muscle, brain, leukocytes, and fibroblasts (5, 9, 12).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the hepatic form, a neuromuscular form of the disease has been reported. These patients may ( a ) present at birth with severe hypotonia, muscle atrophy, and neuronal involvement with death in the neonatal period (8)(9)(10)(11); ( b ) present in late childhood with myopathy or cardiopathy (12)(13)(14); or ( c ) present as adults with diffuse central and peripheral nervous system dysfunction accompanied by accumulation of polyglucosan bodies in the nervous system (so-called adult polyglucosan body disease) (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with APBD usually present between the fourth and the sixth decade of life with a variable combination of symptoms and signs commonly including corticospinal involvement, peripheral neuropathy, bladder dysfunction, and, in about half of the patients, cognitive impairment. 10,21,23,33 A few magnetic resonance imaging (MRI) studies have shown nonspecific, leukodystrophy-like changes in cerebral white matter (WM), along with brain and spinal cord atrophy. 5,22,23,33 Most cases are apparently sporadic but a few familial clusterings involving siblings have been reported.…”
Section: Accepted 17 September 2007mentioning
confidence: 99%
“…Outro exemplo de pesquisa bioquímica semelhante foi a descrição ,em dois pacientes com a doença de inclusão de polissacarídeos do adulto, de redução da atividade enzimática ramificante em polimorfonucleares 13 .…”
Section: Conclusãounclassified